Pengembangan Instrumen Pengukuran Nilai Disiplin Mahasiswa Program Studi Pendidikan Matematika Universitas Flores - Maria Fatima Mei; Stefania Baptis Seto (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2020)
This study aims to produce an instrument for measuring the value of disciplinary attitudes. This research used research and development methods. The population of this study were students of the Mathematics education study program and the samples were taken randomly, totaling 104 students. The data collection technique was in the form of a questionnaire using a Likert scale and distributed to online students using Google Form. The data analysis technique used in this study was the validity of this instrument theoretically with expert judgment, empirically using construct validity with factor analysis. The use of factor analysis was with the help of the SPSS 16.0 program. The reliability of the instrument was determined by calculating the Cronbach Alpha coefficient. Based on the results of the study, it showed that the results of testing on 104 students obtained a data feasibility test analysis with a KMO coefficient> 0.5 which was equal to 0.780 and the correlation between each item MSA coefficient 'a'>0.5 with an average MSA of 0.823. This showed that the instrument for assessing disciplinary attitudes was declared feasible. The results of the analysis of the construct validity of the self-assessment instrument showed that all values were more than 0.5. therefore, it can be concluded that all of the 40 items are valid and spread into 6 factors with an Alpha value of 0.829. These results indicate that the items of the discipline value instrument in the study are reliable.